The Connections between the Basilian Order and Vilnius University - Kažuro, Ina (Lietuvos istorijos studijos, 2018)
[full article and abstract in Lithuanian; abstract in English] Vilnius University has been the preeminent high school of The Grand Duchy of Lithuania for several centuries, spreading its influence across different areas of public life – religion, politics, culture. This article analyzes the influence of the Vilnius Alma Mater on the development of the Order of Saint Basil the Great (which had operated between 1617–1839). To that end, three aspects, revealing the connections of the two establishments, are distinguished: Basilians as university students, Basilians as university professors, and Basilians as university partners in the field of education. The research indicates that over a hundred young Basilians were studying in Vilnius University between 1617 and 1832. The members of the Basilian Order constituted a significant group of monk students from the mid-18th to the early 19th centuries. Cooperation in administering secondary schools yielded mutual benefits for both Vilnius University, which supervised the Vilnius educational district in 1803–1832, and the Basilian Order. The Order secured maintenance and provided support for a certain part of the Vilnius educational district schools, while the University became the protector and representative of the Order’s interests in Russian governmental institutions. The employment of Basilian lecturers (professors and vice-professors) at Vilnius University indicates the public recognition of the Order.